THE IMPLEMENTATION OF ENGAGE, STUDY, ACTIVATE (E.S.A) IN TEACHING ENGLISH FOR SENIOR HIGH SCHOOL - Hidayah, Yulia Nuzulul; Harjali, H (Universitas Pendidikan Ganesha, 2017)
To catch the students interesting in learning is the vital element of teachers’ responsibility. In order to interest the students’ attention, teachers require having adequate teaching methods. One of the teachers’ efforts to engage the students is by applying E.S.A. The current study is intended to examine the implementation of E.S.A (Engage, Study, Activate) in teaching English at the tenth grade of SMA N 1 Dolopo, Madiun. This study applied a qualitative approach by employing in-depth interview, participant observation, and documentation as data collection methods. The results of this study revealed that first, E.S.A can be applied in any lessons and skills of English lesson. Second, the most effective of E.S.A’s procedure is Patchwork because it has unique phases to make good result of students’ achievement. Third, students have different perception toward teacher teaching process using E.S.A. It is expected that this study could provide some recommendations for more effective teaching English.